Prophylaxis of Pain and Fractures within Feet in the Course of Osteoporosis: The Issue of Diagnosing - Aleksandra Bitenc-Jasiejko; Krzysztof Konior; Kinga Gonta; Magdalena Dulęba; Danuta Lietz-Kijak (Pain Research and Management)
Background. Considering the enormous risk of fractures in the course of osteoporosis in the area of the feet, an important aspect of prophylaxis is periodic and, in special cases, ongoing monitoring of defects and deformations as well as pressure distribution. The purpose of this article is to indicate the role of the examination of posture and pressure distribution during standing, postural balance, and gait, in the prevention of fatigue fractures in the course of osteoporosis, based on the literature review and examples of patients. Methods. The manuscript consists of two parts; it has a review-analytical character. The first part reviews the literature. The data were obtained using the MEDLINE (PubMed), as well as Cochrane and Embase databases. The database review was carried out focusing mainly on English-language publications, while taking into account the topicality of scientific and research works in the area of osteoporosis. The problem of multiaspects in the area of bone density was pointed out. Considering the above, in the second part, the authors analyzed 11 exemplary patients with osteoporosis, referring to the assessment of foot and lower limb defects using traditional posturological methods and including pedobarography to diagnostic procedures that are used in the assessment of pressure distribution, standing and moving, and an attempt to balance. Results. Analysis of the research and scientific literature proved the lack of unambiguous diagnostic procedures of the locomotor system recommended for the prevention of fatigue fractures in the course of osteoporosis. The main diagnostic recommendations are imaging tests (most often X-ray), which are recommended in the case of specific clinical symptoms. The analysis of exemplary patients with osteoporosis showed numerous disorders in the distribution of pressure in the plantar part of the feet, which are related, among other things, with their individual defects and lower limbs. Conclusions. Detailed posture diagnostics and gait estimation, along with the analysis of pressure distribution within the feet are a very important aspect of the prevention of structural degradation and fatigue fractures within the feet. An important postulate for further research and scientific work is the elaboration of the procedures that will serve the preventive diagnostics of the locomotor system, aimed at early detection of threats of fatigue fractures.